Electricity Generation under the Climate Change Situation in Latin America: Trends and Challenges - Undurraga, José P.; Rivera, Marco; Cossutta, Pablo; Garcés, Alejandro; Ayala, Magno; Garcia, Leidy Y.; Wheeler, Patrick (International Journal of Energy Economics and Policy, 2024)
In a scenario of energy inequality, countries require stability for development and quality of life for their inhabitants. This paper addresses the reality of access to electrical energy and the effect of climate change on the potential of renewables to propose strategies related to generation and transmission in Argentina, Chile, Colombia and Paraguay. This is done by analysing quantitative and qualitative aspects of the electrical energy matrix: installed capacity and technology for generation and transmission together with the penetration of renewable energies. Among the results, actions address energy poverty, energy efficiency, smart investment in energy, and the readaptation of transmission infrastructure.